A narrative inquiry on Malaysian parents' and caregivers' experiences in detecting autism, seeking interventions, challenges and adaptations - Badariah Bt Sani (Kulliyyah of Education, International Islamic University Malaysia, 2017)
There is a lack of knowledge among Malaysian parents in detecting signs of autism in their children. This situation could lead to late detection and intervention. Children's condition would be harder to improve and this would affect the parents' and caregivers' well-being. Thus, parental awareness and knowledge is important for early diagnosis of autism. This study explored parents and caregivers' experiences in recognising signs of autism, providing intervention for their autistic children at home, coping with their challenges and making adaptations. The study used a qualitative research approach with a narrative inquiry method. A total of eleven respondents were interviewed. In-depth interviews and four non-participant observations were carried out. The study found ten signs of autism that parents and caregivers had noticed in their children's behaviour. Children's delay in speaking was common and the most noticeable sign for all eleven respondents. Respondents admitted having no knowledge and awareness about autism or signs of autism at the beginning. The periods before and after the detection of autism, were difficult periods and many respondents had expressed feelings of sadness, worried as well as frustration. The severity of autism played an important role in alerting parents or caregivers to speed up the process of investigation. Respondents had used many types of interventions for their children and these included behavioural, developmental, family based, therapy based, alternative interventions and medications. Islamic practices were also used by Muslim respondents. Coping strategies used by respondents were problem and emotion focused strategies as well as adaptive and maladaptive strategies. The role of religion as an emotion-focused coping strategy is an important one as it enabled respondents to use a more flexible practice intervention which helped improve their children's development and also overcome their challenges and cope with their lives. Findings from this study gave added knowledge and information on Malaysian parental concerns about the signs of autism, provide suggested interventions for parents, and effective adaptive strategies to face their challenges in caring for the autistic child. The findings are not only beneficial to parents and caregivers but also to teachers, school authorities, practitioners and curriculum developers.